Given that: 3 3 3 3 … = 3 n then n = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Notice that n = 2 1 + 4 1 + 8 1 + ⋯ = 1 − r a 1 , where a 1 is the first term of an infinite geometric series and r is its ratio; therefore the mentioned sum will be : n = n = 2 1 ∑ ∞ a n = 1 − 2 1 2 1 = 1 .
It is given that 3 3 3 3 ⋯ = 3 n ( 1 )
Squaring both sides gives us 3 3 3 3 ⋯ = 3 2 n Dividing by 3 gives us 3 3 3 ⋯ = 3 2 n − 1 ( 2 ) We notice that (2) is exactly the same as (1). So it is legitimate to say 3 n = 3 2 n − 1 ⇔ n = 2 n − 1 Thus, we can say that n = 1 .
3 3 3 3 … = 3 n = 3 × 3 n ⟹ 3 n + 1 = 3 2 n ⟹ n + 1 = 2 n ⟹ n = 1
3 3 3 3 . . . = 3 n
⟹ 3 × 3 n = 3 n
⟹ 3 × 3 n = ( 3 n ) 2
3 n = 3 1
n = 1
Thank you, nice solution.
Let x = 3 3 3 3 …
Then we can replace the part right after the first '3' with x:
x = 3 x
And since stated in the problem that x = 3 n
3 n = 3 ⋅ 3 n
Simplify the right hand side:
3 n = 3 n + 1
Since n = n 2 1 ,
3 n = 3 2 n + 1
Get rid of the base (use lo g
n = 2 n + 1
Multiply both sides by 2
2 n = n + 1
And the last step would be to subtract n from both sides.
n = 1
Therefore, 3 3 3 3 … = 3
Problem Loading...
Note Loading...
Set Loading...
Let x = 3 3 3 3 ⋯ . Then
x x 2 ⟹ x ⟹ n = 3 x = 3 x = 3 = 1 Squaring both sides. Since x = 0
This is quite obvious if we consider the following:
3 3 3 3 ⋯ = 3 3 3 2 = 3 3 2 = 3 2 = 3